The Desmoplastic Stroma Plays an Essential Role in the Accumulation and Modulation of Infiltrated Immune Cells in Pancreatic Adenocarcinoma - Vegard Tjomsland; Lina Niklasson; Per Sandström; Kurt Borch; Henrik Druid; Charlotte Bratthäll; Davorka Messmer; Marie Larsson; Anna Spångeus (Clinical and Developmental Immunology)
Tumor microenvironment is composed of tumor cells, fibroblasts, and infiltrating immune cells, which all work together and create an inflammatory environment favoring tumor progression. The present study aimed to investigate the role of the desmoplastic stroma in pancreatic ductal adenocarcinoma (PDAC) regarding expression of inflammatory factors and infiltration of immune cells and their impact on the clinical outcome. The PDAC tissues examined expressed significantly increased levels of immunomodulatory and chemotactic factors (IL-6, TGFβ, IDO, COX-2, CCL2, and CCL20) and immune cell-specific markers corresponding to macrophages, myeloid, and plasmacytoid dendritic cells (DCs) as compared to controls. Furthermore, short-time survivors had the lowest levels of DC markers. Immunostainings indicated that the different immune cells and inflammatory factors are mainly localized to the desmoplastic stroma. Therapies modulating the inflammatory tumor microenvironment to promote the attraction of DCs and differentiation of monocytes into functional DCs might improve the survival of PDAC patients.